2017
DOI: 10.1093/neuonc/now287
|View full text |Cite
|
Sign up to set email alerts
|

Immunosuppressive tumor-infiltrating myeloid cells mediate adaptive immune resistance via a PD-1/PD-L1 mechanism in glioblastoma

Abstract: Together, these studies elucidate the role that TIMs play in mediating adaptive immune resistance in the GBM microenvironment and provide evidence that they can be manipulated pharmacologically with agents that are clinically available. Development of immune resistance in response to active vaccination in GBM can be reversed with dual administration of CSF-1Ri and PD-1 mAb.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
144
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 138 publications
(147 citation statements)
references
References 47 publications
3
144
0
Order By: Relevance
“…One critical mediator of immunosuppression in GBM is PD-L1 (37,38). While only a fraction of GBM cells express PD-L1 (15,16), myeloid cells in the tumor microenvironment and circulation abundantly express PD-L1 (40). Immunosuppressive myeloid cells are of particular importance in GBM as they extensively infiltrate tumors (26,27) and correlate with decreased survival (28,54).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…One critical mediator of immunosuppression in GBM is PD-L1 (37,38). While only a fraction of GBM cells express PD-L1 (15,16), myeloid cells in the tumor microenvironment and circulation abundantly express PD-L1 (40). Immunosuppressive myeloid cells are of particular importance in GBM as they extensively infiltrate tumors (26,27) and correlate with decreased survival (28,54).…”
Section: Discussionmentioning
confidence: 99%
“…While normally involved in immune homeostasis, in the setting of malignancy, PD-L1 can interact with its receptor, programmed death-1 (PD-1), expressed on activated T cells, to induce T-cell anergy or apoptosis (37)(38)(39). Although PD-L1 is expressed on tumor cells (15,16), evidence suggests that myeloid PD-L1 may contribute more to the suppression of antitumor T cells (40). We have previously reported that elevated peripheral myeloid PD-L1 was associated with reduced response to vaccine immunotherapy and worse survival in patients with GBM (25).…”
Section: Introductionmentioning
confidence: 99%
“…C /PD1 C Tregs could be either minor enforcers of immunosuppression 41 or susceptible to being replaced by T cells expressing alternative immune checkpoints following ICIs treatment. For instance, a recent preclinical study found T cells exploiting T-cell immunoglobulin mucin-3 (TIM3) to drive lung cancer growth despite anti-PD1 therapy.…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, numerous other preclinical studies have highlighted the tumor-promoting and immunosuppressive roles of these cells in GBM [2,[24][25]. However, unlike promising preclinical studies, efforts to deplete TAMCs in GBM patients have been disappointing.…”
Section: Discussionmentioning
confidence: 99%